Interference Control for Cognitive Network with High Mobility. (29th August 2013) - Li, Yuanxuan; Zhu, Gang; Lin, Siyu; Guan, Ke; Ai, Bo
Abstract : Interference control (IC) between the secondary system and the primary system is an important issue for underlay cognitive radio network (CRN). The secondary system should limit the interference power to primary system by adjusting its transmission power. Many relevant works have been done based on the assumption of the quasistatic channel which is not suitable for the fast time-varying fading channel; the performance of IC in underlay CRN will become worse when the channel varies fast. This paper studies the IC issue in high mobility environment. By considering the channel state information (CSI) outdatedness, a short frame structure scheme and a mean interference power constraint scheme are proposed to reduce the influence of CSI outdatedness on IC performance. Furthermore, by considering the channel estimation error, a spherical error region model based robust IC scheme is designed as well. The proposed IC schemes of the secondary system are converted to the power allocation problems, and then they are formulated to optimization problem whose objects are to maximize the capacity of the secondary system with the interference constraints. The above optimization problems are solved by the water-filling style method. The simulation results show that the proposed IC schemes can effectively control the interference power to the primary system.